Gorham-Stout disease with parietal bone osteolysis: a case series and review of literature. (2nd January 2021) - Takaya, Kento; Sakamoto, Yoshiaki; Miwa, Tomoru; Yoshida, Kazunari; Kishi, Kazuo
Abstract: Background: Gorham-Stout disease (GSD) is a rare and idiopathic bone disorder, characterized by massive osteolysis. To date, there is no established treatment strategy for GSD. We empirically treated two patients, who had presented to us with cranial lesions of GSD. Here, we propose a novel algorithm for the management of Gorham's disease based on our experience and review the literature published to date. Methods: We reviewed all existing literature on GSD describing the pathophysiology and suggested treatment methods, up to 2018. Results: We found 13 papers with 14 reported cases; an inclusion of our two cases brings the total count up to just 16 recorded cases of GSD involving the skull. Of these, the base of the skull was affected in eight cases, while the remaining eight cases showed cranial involvement. The patients with skull-base involvement were managed conservatively, using medications or radiotherapy. The patients with cranial osteolysis were managed surgically, with an excision of the osteolytic portion, followed by cranioplasty. Of the latter group, the pericranium was not removed in one patient, in whom a very slight progression of the osteolytic process was later observed. Conclusions: The pathogenesis of GSD remains poorly understood. Further study is required to determine an optimum management strategy. A long-term follow-up will also be necessary to establish the effectiveness of the treatment process. The untreated patients show a progressive resorption of the affected bones of the skull. A painful, vanishing skull deformity is an alarming sign of GSD. Early diagnosis and treatment are necessary to arrest disease progression and to prevent complications.